Analisis Dampak Investasi Cryptocurrency dan Volatilitas Pasar terhadap Profitabilitas Perusahaan Energi di Indonesia - Judijanto, Loso; Utami, Eva Yuniarti; Devi, Erwina Kartika; Sarmiati, Sarmiati; Sudarmanto, Eko (Eastasouth Institute, 2024)
This research investigates the impact of Cryptocurrency investments and market volatility on the profitability of energy companies in Indonesia through quantitative analysis. The study involved a sample of 200 participants, including Cryptocurrency investors and executives of energy companies. Analysis of measurement models establishes construct validity and reliability (Cryptocurrency Investment, Market Volatility, and Profitability), and analysis of structural models reveals significant relationships between these variables. Surprisingly, the results showed that increased Cryptocurrency investments and higher market volatility were associated with increased profitability of energy companies. The model fit index confirms the robustness of the proposed model. The findings have implications for investors, policymakers, and industry stakeholders, who emphasize the need for informed decision-making in navigating the ever-evolving landscape of cryptocurrencies and traditional industries.